(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
The purpose this work was to identify the initial level of development of research skills in primary school students, were conducted experiments on the basis of the identified criteria and indicators of development of research skills: organizational (skills that allow planning and effectively organizing research work); search (skills that provide the ability to find a research problem and select adequate research methods for solving it); information (skills that involve working with literary and technical means of information); evaluative (skills that allow arguing one’s opinion when evaluating one’s own and other people’s work). The results of the experiment showed the need for targeted work on developing research skills in primary school students. During the experiment, a model for developing research skills in primary school students in the context of STEM education was implemented. The main technologies for working on this program were STEM projects and research work. The results of the control section revealed positive dynamics in the levels of development of research skills in primary school students included in the experimental group. These results demonstrate the possibility of using STEM education to develop research skills in primary school students.